Design and Implementation of a 3-Phase Induction Motor Controller Simulator Using Programmable Logic Controller (PLC) and Human Machine Interface (HMI) Integration - Kaleb Priyanto; Immanuel Eltian Sudjana; Hans Nashirudin Almay; Kriswanto; Haikal; Sarai Enita (Infotekmesin, 2026)
This study was conducted as a response to the limited availability of practical learning tools in industrial automation education and training. In this research, a three-phase induction motor control simulator was designed and developed by integrating a Programmable Logic Controller (PLC) and Human Machine Interface (HMI) system. The main objective is to enhance learners' understanding and practical skills in designing and operating industrial control and automation systems through an interactive learning approach. The development process involved designing the system architecture using an Omron CP2E PLC and NB-series HMI, electrical integration, ladder diagram programming, and user interface development. The simulator was then tested to ensure its proper functionality and effectiveness in supporting the learning process. The results demonstrate successful system integration, reliable control logic, and an intuitive user interface via the HMI. This research contributes a structured and cost-effective educational tool that is well-suited for automation engineering and technical training programs.